2017
DOI: 10.1186/s12870-017-1156-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in petals and leaves of chrysanthemums with different chlorophyll levels

Abstract: BackgroundChlorophylls (Chls) are magnesium-containing tetrapyrrole macromolecules responsible for the green color in plants. The Chl metabolic pathway has been intensively studied and nearly all the enzymes involved in the pathway have been identified and characterized. Synthesis and activity of these enzymes are tightly regulated in tissue- and developmental stage–specific manners. Leaves contain substantial amounts of Chls because Chls are indispensable for photosynthesis. In contrast, petals generally cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
6
30
1
Order By: Relevance
“…Recently, an expressed sequence tag database of chrysanthemum cultivar ‘Sei-Marine’ was constructed ( Sasaki et al 2017 ). Based on the database, Ohmiya et al (2017) generated a custom array and performed microarray analyses. Those authors compared the expression levels of chlorophyll-rerated genes among the white petals (absence of chlorophyll), green petals (low level of chlorophyll), and leaves (high level of chlorophyll) of chrysanthemum cultivars to identify the mechanisms of chlorophyll accumulation.…”
Section: Greenmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an expressed sequence tag database of chrysanthemum cultivar ‘Sei-Marine’ was constructed ( Sasaki et al 2017 ). Based on the database, Ohmiya et al (2017) generated a custom array and performed microarray analyses. Those authors compared the expression levels of chlorophyll-rerated genes among the white petals (absence of chlorophyll), green petals (low level of chlorophyll), and leaves (high level of chlorophyll) of chrysanthemum cultivars to identify the mechanisms of chlorophyll accumulation.…”
Section: Greenmentioning
confidence: 99%
“…It is reasonable to assume that factors responsible for suppressing chlorophyll biosynthesis or enhancing chlorophyll degradation exist in white petals. Ohmiya et al (2017) identified several candidate transcription factors, whose expression was closely correlated with the chlorophyll level. Functional analysis of these transcription factors will provide a basis for future molecular studies on organ-specific chlorophyll accumulation.…”
Section: Greenmentioning
confidence: 99%
See 1 more Smart Citation
“…STAY-GREEN protein (SGR, coded by c48794_g1) is a key component of controlling chlorophyll degeneration by destabilizing protein-pigment complexes in the thylakoid membranes [ 42 ]. In Chrysanthemums , Ohmiya et al [ 43 ] show that the expression level of SGR is drastically increased in white mutations. Zeaxanthin epoxidase (ZEP) catalyses the downstream reaction of carotenoid biosynthesis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all enzymes involved in the pathway are identi ed [18][19][20] . Several transcription factors have been reported as regulators of the chlorophyll biosynthesis pathway, such as LONG HYPOCOTYL5 (HY5), GOLDEN2-LIKE (GLK) [21][22][23] . However, limit information is available about the regulation of chlorophyll metabolism in eggplant.…”
Section: Introductionmentioning
confidence: 99%